Description of students learning difficulties in the basic law of chemistry - Vaulia Leoni Putri; Latisma Dj (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2022)
This study aims to determine the percentage of learning difficulties and describe the factors that cause learning difficulties for class X students in the 2021/2022 academic year at SMAN 15 Padang studying the fundamental law of chemistry. The research was descriptive. This research gave a four-tier diagnostic test of 19 questions representing seven learning indicators. In addition, to reveal the causes of students' learning difficulties, a questionnaire consisting of 28 questions was given that represented nine aspects of the causes of students' difficulties, both from internal and external factors. The data obtained in this study were analyzed using descriptive analysis. The results of the research data analysis showed that the students of class X 7 SMAN 15 Padang had learning difficulties, with a high category of 71.1%. And the results of the questionnaire data analysis that caused students' learning difficulties were 62.2%. The highest level of student learning difficulties is found in the 4th indicator of 83.3%, with a very high category. Meanwhile, the lowest level of student learning difficulties is found in the 6th indicator, 52.8%, with a reasonably high category. The factors that cause students' learning difficulties in the basic law of chemistry are seen from internal and external factors, which consist of 9 aspects. The most influential aspect is the family environment of 70.3%, and the lowest aspect is student learning time of 50.0%. The most influential internal factors are the aspects of students' motivation and interest in learning, which are 66.7% and 61.8%, respectively. Family and social environment are the most influential external factors on student learning outcomes, amounting to 70.3% and 64.6%, respectively.